Analisis Kualitas Ekologi Perkotaan Berbasis Data Penginderaan Jauh di Kota Bandung Tahun 2023 - Mahendra, Auzaie Ihza; Murti Budi Santosa, Sigit Heru; Widayani, Prima (Universitas Negeri Yogyakarta, 2024)
Urbanization has consequences for the urban environment, such as environmental pollution, which has a direct impact on the quality of urban ecology. In monitoring the quality of the urban environment, RSEI is one method that can be used. This study aims to assess the quality of urban ecology using RSEI in Bandung City in 2023 during the rainy season and dry season. RSEI combines four main indicators in the form of NDVI, WET, NDBSI, and LST from Landsat 8 and 9 image data analyzed using the PCA method. The results showed that image recording in both seasons greatly affected the RSEI results, where RSEI had better conditions during the rainy season than the dry season in terms of area and spatial distribution. This was evidenced by the RSEI area in the good and very good categories tending to be higher during the rainy season.Keywords: Urban Ecological Quality, RSEI, Landsat